A Non-Anthropomorphic Bipedal Walking Robot with a Vertically Stabilized Base - Ivan Virgala; Ľubica Miková; Tatiana Kelemenová; Martin Varga; Róbert Rákay; Marek Vagaš; Ján Semjon; Rudolf Jánoš; Marek Sukop; Peter Marcinko; Peter Tuleja (Applied Sciences, 2022)
The paper deals with the proposed concept of a biped robot with vertical stabilization of the robot’s base and minimization of its sideways oscillations. This robot uses 6 actuators, which gives good preconditions for energy balance compared to purely articulated bipedal robots. In addition, the used linear actuator is self-locking, so no additional energy is required for braking or to keep it in a stable position. The direct and inverse kinematics problems are solved by means of a kinematic model of the robot. Furthermore, the task is aided by a solution for locomotion on an inclined plane. Special attention is focused on the position of the robot’s center of gravity and its stability in motion. The results of the simulation confirm that the proposed concept meets all expectations. This robot can be used as a mechatronic assistant or as a carrier for handling extensions.